Professional self-development of future domestic science teachers as a relevant problem in the process of their training - Nikolay V. Sayapin (Saratov State University, 2022)
The problem of professional self-development of future domestic science teachers in the process of their training is relevant due to the fact that modern educational institutions need teachers who are able to quickly adapt to sweeping changes and are able to develop independently in the professional field. University training of future domestic science teachers is one of the stages of their professional self-development. The objective of the study is to determine to what extent university training of future domestic science teachers is important for their professional self-development. The objective is achieved through the analysis of regulatory documents, the analysis of scientific research and the results of student questionnaires. The presence or absence of aspects affecting the professional self-development of future domestic science teachers were determined while conducting the analysis of the federal regulatory documents that govern the training process of future domestic science teachers at the university. The analysis was carried out in accordance with the Federal State Educational Standard of Higher Education and the "Teacher" Professional Standard. The Federal State Educational Standard for Bachelor's and Master's degrees includes a directive to develop a competence closely related to the professional development of future domestic science teachers - Universal Competence-6 (UC-6). The analysis of the professional standard of a teacher allows us to distinguish two fundamental roles teachers perform at work. These roles indicate those actions, skills and knowledge that are collectively associated with the professional self-development of teachers. The empirical research was carried out on a sample of students (N = 52, aged 18 to 30 years, women = 60%), majoring in pedagogy (44.03.01 Pedagogical Education with the major in "Domestic Science") at Saratov State University (the city of Saratov). A questionnaire (prepared by N. V. Sayapin) was used to determine to what extent professional self-development is significant. The positive dynamics of the parameters of time spent on professional self-development for senior courses has been revealed. There is a consensus among respondents that professional self-development is an integral component of professional growth and part of competitiveness in the profession. The presented empirical materials can be used in creating pedagogical conditions for the implementation of effective training aimed at professional self-development of students.